PENERAPAN TEKNOLOGI MINI INTEGRATED FARMING SEBAGAI UPAYA PEMULIHAN EKONOMI DAN KETAHANAN PANGAN MASYARAKAT KORBAN GEMPA DI DESA ARGOREJO KECAMATAN SEDAYU KABUPATEN BANTUL - Sonita Rosningsih (Caraka Tani: Journal of Sustainable Agriculture, 2010)
Community service of the mini-integrated aplication program was done in the village of Argorejo, Sedayu, Bantul, Yogyakarta, on May to December 2009, aims to accelerate economic recovery and food avaibility of the earthquake-victim communities in Argorejo village. The group and individual approaches method used for implemented this program. 10 packages of local Hens and 10 packages vertikultur given to 10 selected participants (the status of young housewives) who later formed farmers' group called "Srikandi". Each package consists of 1 head of local cock and 10 local Hens is ready to lay their eggs. Guidance, training and strategy of setting chicken population, and cultivation vertikultur has been implemented . The results of the activities was established 10 poultry farmer who runs a semiintensive business. Vegetable crops are able to consumpt for family need, and vegetable waste for poultry feed. Most of the egg production use for family food needs. Now poultry and vertikultur farm are conscious cheap source of food for the family. Recent developments owned by members of the population groups currently are 100 local Hens, 11 head of cockl, 550 pullet, 300 DOC, 340 hatching eggs (being incubated).